A Review on the Special Radiotherapy Techniques of Colorectal Cancer - Tam, Shing Yau; Wu, Vincent W. C. (Frontiers in Oncology, 2019)
Colorectal cancer is one of the commonest cancers worldwide. Radiotherapy has been established as an indispensable component of treatment. Although conventional radiotherapy provides good local control, radiotherapy treatment side-effects, local recurrence and distant metastasis remain to be the concerns. With the recent technological advancements, various special radiotherapy treatment options have been offered. This review article discusses the recently-developed special radiotherapy treatment modalities for various conditions of colorectal cancer ranging from early stage, locally advanced stage, recurrent and metastatic diseases. The discussion focuses on the areas of feasibility, local control and survival benefits of the treatment modalities. This review also provides accounts of the future direction in radiotherapy of colorectal cancer with emphasis on the coming era of personalized radiotherapy.